1983
DOI: 10.1136/hrt.49.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1-antitrypsin in acute myocardial infarction.

Abstract: SUMMARY Alpha,-antitrypsin serum levels were measured in 48 patients with acute myocardial infarction and in 19 control patients either with coronary heart disease without necrosis, or with neither coronary disease nor inflammation. Alpha,-antitrypsin was significantly raised in the group of patients with acute myocardial infarction. As some patients individually showed no change in alpha,-antitrypsin levels, however, they were divided into two groups according to the maximum serum levels attained. Patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 14 publications
0
22
1
Order By: Relevance
“…In fact, the magnitude of the increase of HDL bound A1AT in this study was much greater than changes found in previous studies that examined the effect of various diseases or therapy on lipoprotein proteome (5,15,16). Additionally, A1AT has been shown to be involved in cardiovascular disease by modulating various inflammatory processes (17,18).…”
Section: Figcontrasting
confidence: 50%
“…In fact, the magnitude of the increase of HDL bound A1AT in this study was much greater than changes found in previous studies that examined the effect of various diseases or therapy on lipoprotein proteome (5,15,16). Additionally, A1AT has been shown to be involved in cardiovascular disease by modulating various inflammatory processes (17,18).…”
Section: Figcontrasting
confidence: 50%
“…In addition, patients with A1AT deficiency are reported to have increased arterial stiffness, indicative of decreased vessel elasticity and an increased risk for CVD (47). Elevations in plasma A1AT were noted in patients following myocardial infarction and, in these patients, greater elevations were correlated with reduced mortality, further supporting a role for this SERPIN in protection against CVD (48). …”
Section: Potential Roles For Protease Regulation By Hdlmentioning
confidence: 85%
“…During the acute phase response, AAT serum concentrations increase above the normal range [79]. In states of infection or inflammation, neutrophils are recruited into the lungs and the plasma concentration of AAT increases [80,81].…”
Section: Mz Level Heterogeneity and Impact Of The Acute Phase Responsementioning
confidence: 99%